383 ECG in biopsy-proven and clinically suspected myocarditis: morpho-functional correlates and prognostic implications. (8th December 2021) - Giordani, Andrea Silvio; Panzarella, Alex; Candelora, Andrea; Marcolongo, Davide; Merola, Chiara; Tarantini, Giuseppe; Basso, Cristina; Marra, Martina Perazzolo; Marcolongo, Renzo; Iliceto, Sabino; Baritussio, Anna; Caforio, Alida Linda Patrizia
Abstract: Aims: A distinction exists between biopsy-proven (BP) and clinically suspected (CS) myocarditis, the latter being an exclusion diagnosis based on clinical and instrumental findings. A clear diagnostic and prognostic role of the ECG in these two groups of patients has not yet been defined. (i) To describe frequency and characteristics of ECG findings in myocarditis, and to assess any difference between CS and BP myocarditis; (2) to identify morpho-functional correlates between ECG and cardiac magnetic resonance (CMR); and (iii) to evaluate the prognostic value of ECG findings. Methods and results: 162 patients were included (median age 36 years, 70% male, median follow-up 32.9 months), 36 with BP and 126 with CS myocarditis. All patients underwent CMR; for ECG-CMR correlates, the ECG nearest in time to CMR was assessed. Surrogate outcome was defined as left ventricular (LV) ejection fraction (EF) <50% and/or NYHA class >I during follow-up. In the entire cohort ECG alterations were numerous: T-wave inversion (TWI) (82%), fragmented QRS (34%), low voltages (14%), ST elevation (STE) (13%). Compared to CS myocarditis, BP myocarditis patients showed higher frequency of non-sinus rhythm (17% vs. 2%, P < 0.001), long QT (28% vs. 0%, P < 0.001), lateral TWI (36% vs. 19%, P = 0.031) and bundle branch block (19% vs. 2%, P < 0.001). BP myocarditis patients had worse clinical features at diagnosis: heart failure (64% vs. 6%, P < 0.001), arrhythmic (14% vs. 4%, P = 0.029) and fulminant presentation (14% vs. 0%, P < 0.001), and presented higher LV end-diastolic volume and lower LVEF by echocardiography and CMR (109.5 mL/m 2 vs. 85.50 ml/m 2, P < 0.001; 31.5% vs. 59%, P < 0.001). A correlation was observed between number of myocardial segments with oedema at CMR and low ECG voltages ( P = 0.010) and between late gadolinium enhancement (LGE) mass at CMR and lateral STE ( P = 0.004 and P = 0.049, respectively). Several ECG alterations correlated with the surrogate outcome: long QT ( P = 0.029), lateral TWI ( P = 0.006), left bundle branch block ( P < 0.001), ventricular ectopic beats ( P = 0.020), and atrial fibrillation ( P < 0.001). Conclusions: A significant difference in ECG findings between CS and BP myocarditis has been demonstrated: ECG alterations are more frequent and more severe in BP myocarditis and correlate with prognosis. Moreover, ECG alterations identified patients with pathologic morpho-functional correlates.